PENGARUH LEVERAGE, FINANCIAL DISTRESS, TAX PLANING, PROFITABILITY DAN INSTITUSIONAL OWNERSHIP TERHADAP EARNINGS MANAGEMENT - Rashif Yahya Anshari; Eny Kusumawati (Jurnal Akuntansi dan Pajak, 2024)
Earnings management is a management effort to smooth profits by maximizing or minimizing profits, including smoothing profits in accordance with the intention of management's personal interests. This research aims to analyze the influence of leverage, financial distress, tax planning, profitability, and institutional ownership on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used in this research was purposive sampling. A total of 222 companies have met the criteria as observation units. The analytical method used is multiple linear regression analysis. The research results provide empirical evidence that financial distress and profitability effects earnings management. Meanwhile, leverage, tax planning and institutional ownership do not effect on earnings management.